Thiosulphate sulfurtransferase: Biological roles and therapeutic potential - Luo, Yang; Melhem, Shaden; Feelisch, Martin; Chatre, Laurent; Morton, Nicholas M.; Dolga, Amalia M.; van Goor, Harry (Redox biology, 2025)
Mitochondria are central to eukaryotic cell function, driving energy production, intermediary metabolism, and cellular homeostasis. Dysregulation of mitochondrial function often results in oxidative stress, a hallmark of numerous diseases, underscoring the critical need for maintaining mitochondrial integrity. Among mitochondrial enzymes, thiosulfate sulfurtransferase (TST) has emerged as a key regulator of sulfur metabolism, redox balance, and Fe–S protein maintenance. Beyond its well-known role in cyanide detoxification, TST facilitates hydrogen sulfide (H2S) metabolism by catalyzing the transfer of sulfur from persulfides (R–SSH) to thiosulfate (S2O32−), promoting H2S oxidation and preventing its toxic accumulation. Additionally, TST contributes to the thiol-dependent antioxidant system by regulating reactive sulfur species and sustaining mitochondrial functionality through its role in sulfide-driven bioenergetics. This review highlights the biochemical and therapeutic significance of TST in mitochondrial and cellular health, emphasizing its protective roles in diseases associated with oxidative stress and mitochondrial dysfunction. Dysregulation of TST has been implicated in diverse pathologies, including specific metabolic disorders, neurological diseases, cardiovascular conditions, kidney dysfunction, inflammatory bowel disease, and cancer. These associations underline TST's potential as a biomarker and therapeutic target. Therapeutic strategies to activate the TST pathway are explored, with a focus on sodium thiosulfate (STS), novel small molecule (Hit 2), and recombinant hTST protein. STS, an FDA-approved compound, has demonstrated antioxidant and anti-inflammatory effects across multiple preclinical models, mitigating oxidative damage and improving mitochondrial integrity. A slow-release oral formulation of STS is under development, offering promise for expanding its clinical applications. Small molecule activators like Hit 2 and hTST protein have shown efficacy in enhancing mitochondrial respiration and reducing oxidative stress, though both reagents need further in vitro and in vivo investigations. Despite promising advancements, TST-based therapies remain underexplored. Future research should focus on leveraging TST's interplay with pathways like NRF2 signaling, investigating its broader protective roles in cellular health, and developing targeted interventions. Enhancing TST activity represents an innovative therapeutic approach for addressing mitochondrial dysfunction, oxidative stress, and their associated pathologies, offering new hope for the treatment of diseases associated with mitochondrial dysfunction. [Display omitted] •The mitochondrial interaction between oxidative stress and TST.•The extra-mitochondrial impact of TST on NRF2 signaling.•Tissue expression profile of TST in various diseases.•Therapeutic potential of TST activation.